The Force of the Argument Source: The Partiality of the Source Influences the Evaluation of Political Arguments - Herne, Kaisa; Sipinen, Josefina; Kestilä-Kekkonen, Elina; Mattinen, Laura; Söderlund, Peter (Frontiers in Communication, 2022)
We study the influence of argument sources on argument quality evaluations. Argument source refers to the person who present the argument. We ask whether partial, impartial and reluctant sources generate different evaluations of argument quality. We explore the source effect via a survey experiment where participants are asked to evaluate the quality of political arguments. Previous research on source partiality mainly concerns persuasion. that the results suggest that source characteristics such as expertise and trustworthiness affect the persuasiveness of communication. Both impartial and reluctant sources have been observed to promote persuasion, whereas partial sources tend to hinder it. However, the evidence on the difference between impartial and reluctant sources are inconclusive, and research on argument quality evaluations is scarce. In our study, respondents are randomly allocated into four conditions according to who presents a political argument: Control (no argument source); Partial Source, Reluctant Source and Impartial Source. Our results show that overall impartial sources give rise to higher evaluations of argument quality in comparison to reluctant sources, but not in comparison to partial sources. Furthermore, reluctant sources are also perceived low in credibility.